Opposing effects of input control and clan control for sellers on e-marketplace platforms - Evgheni Croitor; Dominick Werner; Martin Adam; Alexander Benlian (Electronic Markets, 2021)
E-marketplace platforms focus on attracting and retaining sellers to secure the platform's long-term viability and success. Although sellers' behavioral intentions have been linked to control modes deployed on e-marketplace platforms, little is known about how and why perceptions of input control and clan control affect sellers' crucial behavioral outcomes. Drawing on IS control literature, we conducted two online surveys with sellers on Amazon (n0.167em=0.167em286) and Etsy (n0.167em=0.167em185). Our results revealed that perceived input control had a negative effect on sellers' perceived usefulness, satisfaction, and continuance intentions, whereas positive effects were observed with perceived clan control. In addition, we find that intrinsic motivation mediates the observed direct effects. Our study contributes to the literature by introducing control modes in the context of e-marketplace platforms and examining the effects of input control and clan control on sellers' beliefs, attitudes, and behavioral intentions. Furthermore, our study has important practical implications for platform providers in how to apply different control mechanisms and increase complementors' willingness to keep contributing to e-marketplace platforms, thereby nurturing platform health and sustainability.
Keywords: D4; O3; 620; Input Control; Clan Control; E-Marketplace Platforms; Intrinsic Motivation; Continuance Intention